Title Representation of the Main Character's Emotions in Nadzira Shafa's Novel 172 Days: : A Psychological Perspective - Bella , Bella Indriyani Putri; Ghufroni; Nurchalistiani Budiana (Universitas Swadaya Gunung Jati, 2025)
Bella Indriyani Putri. (2025). Representation of the emotions of the main character in the novel 172 days by Nadzira Shafa Psychological perspective, Indonesian Language and Literature Education. Muhadi Setiabudi University Brebes. This study aims to analyze what emotions are in the character Zira (main character) and how these emotions can represent the psychology of the character Zira (main character) in the novel 172 Days by Nadzira Shafa using Sigmund Freud's literary psychology theory. The research method used in this study is descriptive qualitative with the data source of the novel 172 Days Krya Nadzira Shafa. The research data are in the form of phrases or sentences and dialogues in the novel that represent the emotional psychology of the main character in the novel